Проблеми ведення підготовчих робіт на вугільних шахтах України та напрями їх вирішення - Makarov V.M. (General Energy Institute of the National Academy of Sciences of Ukraine, 2004)
Experience of using the entry-driving techniques of a new technological level of a domestic production on Ukrainian collieries in different mountain-geological conditions is analyzed. The estimation of prospects of its application is executed.